Respon Time Perawat dengan Penanganan Keluhan (Complain Handling) Keluarga Pasien di Instalasi Gawat Darurat - Gabriella Julia Kandou; Silvia Dewi Mayasari Riu; Zainar Kasim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Nurses need to improve the quality of their responses and complaint handling in serving patients, so that the quality of nursing services can be considered good and patients feel satisfied. In conditions of response time, healthcare personnel, especially nurses, are required to provide quick, accurate, and holistic handling immediately. The objective of this study is to determine the relationship between nurses' response time and family complaint handling in the Emergency Room of RSUD Maria Walanda Maramis. The research uses a cross-sectional design. The sample in this study consisted of 68 respondents using the purposive sampling technique. Data collection on response time and complaint handling was conducted using observation sheets and questionnaires, and analyzed using the chi-square statistical test. The research results showed that the most common response time was the quick response time category, with 61 respondents (89.7%), and the most common complaint handling was in the good category, with 59 respondents (86.8%). The result of the chi-square test obtained a p-value of 0.004 where < α 0.05. Conclusion: There is a relationship between the nurses' response time and the handling of family complaints in the Emergency Room of RSUD Maria Walanda Maramis. Patient families are expected to provide constructive feedback regarding the emergency department services so that the hospital can continue to improve the quality of its services.